Population dynamics of mango mealybug (Drosicha mangiferae) (Margorididae: Hemiptera) and its relation with weather parameters in subtropical climatic conditions - GUNDAPPA, GUNDAPPA; ADAK, TARUN; SHUKLA, P K (The Indian Journal of Agricultural Sciences, 2018)
Dynamics of mango mealybug (Drosicha mangiferae Green) in the mango (Mangiferae indica L.) growing agro-ecology of Lucknow region of Uttar Pradesh, India was studied during three seasons (2013-2015). Wider variations in the occurrence of mango mealybug were inferred from the study across 22 locations and three seasons. Weekly average mealybug incidence was tabulated against standard meteorological weeks (SMW), a range of 0.09to 2.05, 0.13 to 1.57 and 0.11 to 2.56 mealybug per panicle during 2013, 2014 and 2015 was observed respectively. Peak incidence of 2.05, 1.57 and 2.10 mealybug per panicle was observed at mango orchards of Ulrapur (Fixed II), Navipana (Fixed I) and Ulrapur (Fixed I) respectively. The peak incidence of mango mealybug was found at 7th, 3rd, 10th SMW during the mango seasons of 2013 2014 and 2015 respectively. The mango mealybug incidence had significantly positive relation with maximum relative humidity and rainfall across the seasons. The linear regression models had explained upto 61% of variation in the mealybug population with the weather variables. Thus theÂ  concluded wide spread dynamics of mango mealybug incidence across mango orchards of 22 locations. The seasonalchanges were also depicted.